AN OVERVIEW ON UTILIZATION OF NATURAL GAS COMBUSTION FLUE - Chaerul Qalbi Am (OISAA, 2020)
A brief overview and comparison of methods to utilize the Natural Gas Combustion Flue stream. An increase in natural gas usage as fuel and its unique combustion characteristics call for specific waste heat optimization methods. Successful natural gas combustion flue waste heat utilization methods exhibit certain phenomenons. From the overview, it is also discovered that the common waste heat method can be applied to natural gas combustion flue, although the specific condition is required. This paper divides the methods into three categories, non-contact heat exchanger, direct-contact heat exchanger, and thermoelectric generations. Discussions on the result and what affects it are present as well as further studies that can be conducted to expand our scope of knowledge of the subject.